Undergraduate Students’ Perception on Using Ome TV as a Tool in Improving English Speaking Skill - Jalil, Hasibul; Islam, Muhammad Hifdil; Hamdany, Beny (Journey: Journal of English Language and Pedagogy, 2024)
One of the obstacles in learning English as a foreign language, especially speaking skills, is the lack of practice outside the classroom. In this globalization era, there are a lot media available that can be used as learning tools, using Ome Tv, a social media platform that can be used as a useful alternative for practicing English speaking skills outside the classroom. This research aims to find students' perceptions on the use of Ome Tv to improve their English speaking skills. This research uses a Qualitative Descriptive Method. This research uses interviews to collect data. The participants in this research were six Students of English education department. The results of this research reveal that Ome Tv provides English learners the opportunity to practice speaking English with foreigners from various countries via video chat. Using Ome Tv is very effective for improving English speaking skills which include fluency, pronunciation, expanding vocabulary, and improving English communication skills. Ome Tv is effective for English speaking skills but Ome Tv is not effective for aspects of English accuracy because Ome Tv is a random video chat